Thermal Power Plant Equipment and Environmental Impact (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Working principle of natural circulation drum steam boiler: Combustible mixture is fed to the combustion structure. The fuel combustion process does not take place here. The task of the combustion structure is to ensure good mixing of fuel and air. The combustible mixture is fed into the combustion chamber, where a high temperature (up to 2000 °C) is obtained as a result of the combustion process. Part of the heat is given to the evaporator tubes located on the inner walls by radiation. As a result, a water vapor mixture is formed inside the pipe. As a result of the density difference, the water-steam mixture moves towards the drum. Water and steam are separated here. Steam from the drum is fed to the steam heater and from there to the turbine. Feed water is supplied to the drum in the amount of this steam. This water, in turn, is heated to a certain temperature in the economizer.